Tatana traditional costume and its effect on Tatana youths’ ethnic affirmation in Kuala Penyu, Sabah, Malaysia - Getrude C. Ah Gang @Grace (Scholarly Communications Outreach Coordinator Grand Valley State University Libraries, 2024)
The Tatana is one of the indigenous groups of the Malaysian state of Sabah. Their language is said to be related to the Murutic family, with some influences from the neighboring Bisaya, who speak a Dusunic language. They are the largest ethnic group residing in Kuala Penyu, on the southwestern peninsula of Sabah. One of the unique features of the Tatana culture is its beautiful traditional costumes, called the sira lambung for females, and the sira dambia for males. The traditional costume is commonly worn during significant occasions, such as the harvest festival, Tatana annual Odou Bakanjar events, and wedding ceremonies. The traditional costume symbolizes the identity of the Tatana and is inherited from the ancient ancestors. It is suggested that this cultural heritage can strengthen the Tatana ethnic identity. To explore the role of Tatana traditional costume, 69 Tatana youths from various villages in the Kuala Penyu district took part in this research study. The study aimed to examine the impact of the traditional Tatana costume on ethnic affirmation among Tatana youths. The study found that the possession of a traditional Tatana costume contributed 9.6% to the variance in Tatana youths’ ethnic affirmation. In addition, the frequency of wearing the traditional costume contributed 9.4% to the variance in ethnic affirmation. ‘Ethnic affirmation’ in this study refers to how Tatana youths identify themselves with their community through their relationships, engagement in community activities, pride in their cultural heritage, and interactions with in-group members. The findings may provide a glimpse of hope to the Tatana community that the younger generation still treasures their traditional costumes, which symbolize their ethnic affirmation.